Mitigation versus adaptation: The political economy of competition between climate policy strategies and the consequences for developing countries - Axel Michaelowa (Hamburg Institute of International Economics (HWWA), 2001)
So far, the dominant paradigm in international climate policy has been mitigation while adaptation has been a low-key issue. However, with LDCs starting to push for adaptation side payments it has recently gained importance. The allocation of funds and the definition of adaptation activities are currently being discussed. The most outstanding difference between mitigation and adaptation is that mitigation activities contribute to a global public good whereas most forms of adaptation are club goods. Technical adapation such as building sea-walls can be distinguished from societal adaptation, e.g. different land-use patterns. Generally, there is a trade-off between mitigation and adaptation strategies as resources for climate policy are limited. The choice between mitigation and adaptation strategies depends on the decision-making context. While mitigation will be preferred by societies with a strong climate protection industry and low mitigation costs the voters' quest for adaptation is linked to the occurence of extreme whether events. The policy choice in industrialised countries feeds back on the situation in developing countries. Adaptation in industrialised countries enhances the adaptation need in developing countries through declining mitigation activities. Unless this adaptation is financed by industrialised countries, developing countries will be worse off than in a mitigation – only strategy. – – Bisher hat sich die internationale Klimapolitik auf die Emissionsvermeidung konzentriert, während die Anpassung an veränderte klimatische Bedingungen eine untergeordnete Rolle gespielt hat. Durch die Forderung der ärmsten Entwicklungsländer nach Unterstützung bei der Anpassung hat sich die Aufmerksamkeit für diese Thematik in jüngster Zeit jedoch erhöht. Zur Zeit wird über die Alloziierung von Geldern und die Definition von Anpassungsaktivititäten verhandelt. Der größte Unterschied zwischen Emissionsvermeidung und Anpassung liegt in der Tatsache, dass es sich bei ersterem um den Beitrag zu einem globalen öffentlichen Gut handelt, während letzteres den Charakter eines Clubguts trägt. Hierbei kann zwischen technischer Anpassung, z.B. Deichbau und gesellschaftlicher Anpassung unterschieden werden. Ein Beispiel für letzteres ist die Nicht-Bewirtschaftung von Küstenregionen. Zwischen Anpassungs- und Vermeidungsaktivitäten besteht aufgrund begrenzter Ressourcen ein Zielkonflikt. Welche Strategie bevorzugt wird hängt u.a von der Stärke der Klimaschutzindustrie eines Landes sowie von dem Auftreten extremer Wetterereignisse in der Vergangenheit ab. Entwicklungsländer bevorzugen eine reine Vermeidungsstrategie auf Seiten der Industrieländer.
Keywords: 330; Klimaschutz; Internationale Umweltpolitik; Immissionsschutz; Klimaveränderung; Wirtschaftliche Anpassung; Public Choice; Nord-Süd-Beziehungen; Welt